Reconstructing the History of Jatropha Introduction and Commoditization in Indonesia - Widjaja, Henky (History Department, Semarang State University and Historian Society of Indonesia, 2022)
This article discusses the history of jatropha in Indonesia, an oil producing plant, which was praised globally as a miracle crop in the first decade of 2000s. After its recent global failure, scientists started to acknowledge the existing insufficient knowledge about this crop. While many current studies on jatropha are focusing on the agronomic, socio-economic and technical aspects of this plant, little effort has been dedicated to explore its historical aspect. This article will specifically contribute to address the absence of clear historical reconstruction of jatropha in Indonesia. The reconstruction is important to present the actual history of the past regarding the cultivation and the application of jatropha. This article addresses the following questions: Have the cultivation and application of jatropha curcas as biofuel been taken place since the Japanese administration period in Indonesia? If not, what was the actual history of biofuel crop cultivation and application at that period of time? How did the popular claims on jatropha history link to the creation of Jatropha hype? The answers of the questions are essential to understand why until today little experiences, knowledge and technologies are available on the ground for both jatropha cultivation and oil processing either at the farm level and industrial scale.Artikel ini membahas tentang sejarah jarak pagar di Indonesia, tanaman penghasil minyak yang dipuji secara global sebagai tanaman ajaib pada dekade pertama tahun 2000-an. Setelah kegagalan global baru-baru ini, para ilmuwan mulai mengakui kurangnya pengetahuan yang ada tentang tanaman ini. Sementara banyak penelitian terkini tentang jarak yang berfokus pada aspek agronomi, sosial-ekonomi dan teknis tanaman ini, sedikit upaya telah didedikasikan untuk mengeksplorasi aspek sejarahnya. Artikel ini secara khusus akan memberikan kontribusi untuk menjawab tidak adanya rekonstruksi sejarah jarak pagar yang jelas di Indonesia. Rekonstruksi ini penting untuk menyajikan sejarah aktual masa lalu mengenai budidaya dan penerapan jarak pagar. Artikel ini menjawab pertanyaan-pertanyaan berikut: Apakah budidaya dan penerapan jarak pagar sebagai bahan bakar nabati sudah dilakukan sejak masa pemerintahan Jepang di Indonesia? Jika tidak, bagaimana sebenarnya sejarah budidaya dan aplikasi tanaman biofuel pada periode tersebut? Bagaimana klaim populer tentang sejarah jarak pagar terkait dengan penciptaan hype jarak pagar? Jawaban dari pertanyaan-pertanyaan tersebut sangat penting untuk memahami mengapa sampai saat ini hanya sedikit pengalaman, pengetahuan dan teknologi yang tersedia di lapangan baik untuk budidaya jarak pagar maupun pengolahan minyak baik di tingkat petani maupun skala industri.Cite this article: Widjaja, H. (2022). Reconstructing the History of Jatropha Introduction and Commoditization in Indonesia. Paramita: Historical Studies Journal, 32(1), 57-66. http://dx.doi.org/10.15294/paramita.v32i1.31277